Yellow Nail Syndrome with Bilateral Pleural Plaques and Diffuse Pleural Thickening: A Mimic of Asbestos Related Disease - Adam Dallmann; Richard L. Attanoos (Case Reports in Pulmonology)
Yellow nail syndrome is a rare acquired condition of unknown aetiology associated with distinct nail discolouration/xanthonychia, pulmonary manifestations, and lymphoedema. Pleural plaques and diffuse pleural thickening are typically, although not exclusively, recognised as markers of prior commercial asbestos exposure. The presence of such biomarkers may assist an asbestos personal injury evaluation. A postmortem examination performed on a 72-year-old man with known long-standing yellow nail syndrome identified pleural plaques and diffuse pleural thickening. An evaluation of the occupational history identified no known asbestos exposure. Electron microscopic mineral fibre analysis detected no asbestos fibres. To the best of our knowledge, this is the only case of yellow nail syndrome in which these benign pleural changes are reported ex asbestos. Alternate causes for such pleural pathology were absent. There is merit in physicians and pathologists having an awareness of these new manifestations when considering claimed asbestos related changes during life and at postmortem.